Pengaruh Market Share dan Intellectual Capital terhadap Kinerja Keuangan Perbankan Syariah di Indonesia - Ellis Al Shadeni; Erinos NR (Jurnal Eksplorasi Akuntansi, 2022)
Financial performance is an activity of analyzing financial statements that is to see how far the company has carried out its duties in accordance with the established financial implementation rules. The purpose of this study is to determine the effect of market share and intellectual capital with the VAIC method, there are VACA, VAHU and STVA on the financial performance of Islamic banking. This study uses quantitative data using multiple linear regression data analysis. The population in this study were Islamic banks registered in Indonesian banking in 2014-2019. The results of this study indicate that the market share has no significant effect on the financial performance of Islamic banking. VACA, VAHU and STVA has no significant effect on the financial performance of Islamic banking.